Development of a new multi-criteria decision-making method - Dua, Tran Van (Eastern-European Journal of Enterprise Technologies, 2023)
Choosing the best option out of the many available options is always the goal to be achieved in all areas. However, the parameters (criteria) in each alternative are not the same, sometimes contradictory. In this situation, choosing the best option is an extremely difficult decision for the decision maker. Multi-criteria decision making (MCDM) is the ranking of alternatives based on the criteria of each alternative. More than one hundred multi-criteria decision-making methods have been proposed by the inventors. They are being used in many different fields. However, for decision makers, choosing an appropriate method to use in each specific case is a difficult task. CURLI (Collaborative Unbiased Rank List Integration) is a multi-criteria decision making method that distinguishes it from all others. That difference is reflected in the fact that when applying this method, the decision maker does not need to normalize the data nor determine the weights for the criteria. However, it will take a long time for decision makers to apply this method, especially when the number of options to rank is large. This study carried out the development of a new MCDM method based on the CURLI method. This new method is named CURLI-2. Many different examples are presented to evaluate the effectiveness of the proposed method. In each example, the result of ranking the alternatives using the CURLI-2 method has been compared with those using other different MCDM methods. The best alternative determined when using the CURLI-2 method always coincides with the use of existing MCDM methods. Using CURLI-2 method to rank alternatives will be much faster and simpler than using CURLI method. This is the advantage of CURLI-2 method compared with CURLI method